Perancangan Ulang Signage dan Wayfinding untuk Meningkatkan Brand Image pada Studi Kasus di Owabong Waterpark - Anggis Rizky Wiyaringtyas; Donny Trihanondo; Siska Noviaristanti (SPECTA Journal of Technology, 2021)
Owabong Waterpark is a water tourism object located in Purbalingga District, Central Java. With the title as the most complete water tourism in Central Java, the Owabong Waterpark brand is famous. However, this phenomenon is not supported by the existence of signage and wayfinding as visual identities and information media. The lack of visible signage and wayfinding as directional media and the inconsistency of signage and wayfinding designs make it difficult for visitors to find information. Currently, the existence of signage and wayfinding does not only function as a signpost that can only be appreciated or seen. More than that, for the company itself, innovation from signage and wayfinding can also function as a business medium that can increase company revenue. To create solutions to existing problems, signage and wayfinding designs were developed. The research was conducted using literature methods, observation, interviews, and questionnaires with the results of the Owabong Waterpark signage and wayfinding need a redesign. By carrying out in-depth research and planning a design concept that is mature and in accordance with the existing phenomena in Owabong Waterpark, it is hoped that it will be the right solution to respond to signage and wayfinding problems.